Effect of Hypnoteaching Methods Toward Cognitive Learning Outcomes to Nervous System Subject in SMAN 97 Jakarta - Sari, Yolanda Holinda; Rusdi, R; Rahayu, Sri (Universitas Negeri Jakarta, 2015)
Learning results are influenced by 2 factors; internal and external factors. Method of learning is one of external factors. This study aimed to determine the effect of Hypnoteaching method toward application the cognitive learning outcomes on Nervous System Topic at SMAN 97 Jakarta. The research was conducted in the second semester of Academic Year 2014/2015. The method was a quasi-experimental with pretest-posttest control group design. A total sample of 74 students of class XI MIA was selected by simple random sampling technique. This research used a cognitive learning. Test instrument data was analized by analysis of variance of the path of non-parametric Kruskal Wallis. The result showed a significance value 0.07> 0.05 so that it was conclude that Hypnoteaching method had no effect on students cognitive learning outcomes Nervous System Topic.